Adhesion force measured by atomic force microscopy for direct carbon fiber-epoxy interfacial characterization. (5th May 2018) - Zheng, Nan; He, Jinmei; Gao, Jiefeng; Huang, Yudong; Besenbacher, Flemming; Dong, Mingdong
Highlights: A novel technique to study the interfacial adhesion in carbon fiber/epoxy composite by atomic force microscopy was proposed. The adhesion forces between three types of carbon fibers and epoxy functionalized tip were measured. Adhesion force results demonstrate the direct effect of surface chemistry of carbon fiber on the interfacial adhesion. Adhesion force measurement has excellent correlation with single fiber microbond test on the carbon fiber/epoxy composite. Graphical abstract: Unlabelled Image Abstract: Adhesion force measurement by Atomic force microscopy (AFM) is used to investigate the interfacial interaction of the carbon fiber (CF)/epoxy composite for the first time. The epoxy functionalized AFM tip and three types of carbon fibers with different surface chemistry and morphologies were used in this study. Results show that the Bis (3-aminophenyl) phenyl phosphine oxide (BAPPO) modified CF possesses a much larger adhesion force (72.7 nN) than the as-received and de-sized CF (22.5 nN and 17.9 nN, respectively) due to formation of the chemical bonding between the BAPPO modified CF and the epoxy functionalized tip. Single fiber microbond test demonstrates that the interfacial shear strength (IFSS) of BAPPO modified CF/EP composite is 15% and 22% larger than that of as-received and de-sized CF/EP, respectively. This nanoscale manipulation by AFM provides a new avenue to measure the interfacial adhesion between the CF and epoxy at the molecular level.